Designing an Adversarial Model Against Reactive and Proactive Routing Protocols in MANETS: A Comparative Performance Study - A. Peda Gopi; E. Suresh Babu; C. Naga Raju; S. Ashok Kumar (Institute of Advanced Engineering and Science, 2015)
Mobile ad-hoc networks are self-organized infrastructure less networks that consists of mobile nodes, which are capable of maintaining and forming the network by themselves. Recently, researchers are designed several routing protocols on these networks. However, these routing protocols are more vulnerable to attacks from the intruders, which can easily paralyze the operation of the network due to its inherited characteristics of MANETS. One such type of attack is wormhole attack. Because of its severity, the wormhole attack has attracted a great deal of attention in the research community. This paper compares reactive and proactive routing protocols in adversarial environment. Specifically, wormhole attack is applied to these routing protocols to evaluate its performance through simulation. Comprehensively the results shows the comparative performance of these protocols against wormhole attack is hard to detect and easy to implement.